Di[2,6-bis(5-phenylpyrazol-3-yl)pyridine]Co(II): an old coordination mode fora novel supramolecular assembly - Scicluna, T.; Fraser, B.; Gorham, Nicole; Maclellan, J.; Massi, Massimiliano; Skelton, B.; St Pierre, T.; Woodward, R. (The Royal Society of Chemistry, 2010)
CoCl2 was treated with 1, 2, and 6 eq. of 2,6-bis(5-phenylpyrazol-3-yl)pyridine (H2L) yielding respectively the monosubstituted [Co(H2L)Cl2], the disubstituted [Co(H2L)2][PF6]2, and a supramolecular assembly formed by a central disubstituted octahedral complex and four more hydrogen bonded peripheral ligands, [{Co(H2L)2}(H2L)4][PF6]2, as illustrated by X-ray crystal structure analysis.